Public health risk associated with the co-occurrence of aflatoxin B1 and ochratoxin A in spices, herbs, and nuts in Lebanon - Daou, Rouaa; Hoteit, Maha; Bookari, Khlood; Joubrane, Karine; Khabbaz, Lydia Rabbaa; Ismail, Ali; Maroun, Richard G.; Khoury, André el (Frontiers in Public Health, 2023)
Background Aflatoxin B1 and ochratoxin A are mycotoxins produced by filamentous fungi that attack crops on field and storage. Both mycotoxins present a risk on public health since aflatoxin B1 is a hepatotoxic and hepatocarcinogenic agent while ochratoxin A can be nephrotoxic. Those mycotoxins can be found in several food items including spices, herbs, and nuts. Objectives In Lebanon, few studies address aflatoxin B1 and ochratoxin A contamination in spices, herbs, and nuts. So, the aim of this study is to investigate the concentrations of those two mycotoxins particularly in spices and herbs and the concentration of aflatoxin B1 in nuts, and to determine the dietary exposure of the Lebanese population and their possible attribution to liver cancer and renal damage. Methods In this work, a total of 198 samples of spices, herbs, and nuts were collected from different sites. Aflatoxin B1 and ochratoxin A were quantified using immune-affinity columns. A food frequency questionnaire was used to quantify the consumption of spices, herbs, and nuts in Lebanon. Exposure to aflatoxin B1 and ochratoxin A was calculated accordingly and liver and kidney cancer risks were evaluated. Results Aflatoxin B1 was respectively found in 100, 20.4, and 98.6% of the spices, herbs, and nuts samples, while ochratoxin A was found in 100 and 44.4% of spices and herbs, respectively. Aflatoxin B1 was found at mean concentration of 0.97, 0.27, and 0.40 μg/kg in spices, herbs, and nuts, respectively while ochratoxin A was found at mean concentrations of 38.8 and 1.81 μg/kg in spices and herbs, respectively. Aflatoxin B1 occurrence was shown to be associated in this study with 0.017 additional cancer cases per 100,000 persons per year, and ochratoxin A weekly exposure was shown to be 5.04 ng/kg bw less than the Provisional Tolerable Weekly Intake of 100 ng/kg bw which indicates low risk of renal damage from spices and herbs consumption. Conclusion The consumption of spices, herbs, and nuts in Lebanon could lead to an increase in health risks associated with aflatoxin B1 and ochratoxin A, specifically spices. The reported occurrence may be directly related to poor storage conditions.